Fiscal policy and growth with complementarities and constraints on government - Florian Misch; Norman Gemmell; Richard Anthony Kneller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper considers the implications of complementarity in private production and constraints on government for optimal fiscal policy. Using an endogenous growth model with public finance, it derives three central results which modify findings in the literature under standard assumptions. First, it shows that optimal public spending composition and taxation are interrelated so that first- and second-best fiscal policies differ. Second, it shows that the growth-maximizing fiscal policy is affected by preference parameters. Third, it shows that with budget rigidities and informational limitations, knowledge about the optimal fiscal policy parameter values is not necessary for growth-enhancing fiscal policy adjustments.
Keywords: E62; H21; H50; O40; 330; Imperfect Knowledge; Economic Growth; Productive Public Spending; Optimal Fiscal Policy